THE ANALYSIS OF FLOUTING OF CONVERSATIONAL MAXIMS ON THE MAIN CHARACTERS IN “ MOANA” MOVIE - Dini Nurfarwati; Siti Nur Anisa; Rasi Yugafiati (PROJECT (Professional Journal of English Education), 2018)
This study focuses to analise the flouting of conversational maxims which are found in Moana movie. The study uses mix method. There are four of maxims can be revealed. The first is maxim relevance. The reasons of maxim relevance are:“The Maui’s responses do not appropriate to Moana’s statements” and “Moana’s response does not appropriate to Maui’s statement”. The second is maxim manner.The reason of maxim manner are: “Moana’s statements do not clear”, “Maui’s response does not appropriate to Moana’s statement”, and “Maui’s statement does not clear”. The third is maxim quantity. The reasons of maxim quantity are: "The Maui’s responses do not appropriate to Moana’s statements”, “Moana’s responses do not appropriate to Maui’s statement”, “Maui’s statement is flouting the maxim”, and “Moana’s steatment is flouting the maxim”. The forth is maxim quality. The reason is “Maui’s responses contain lies”. that among 4 types of maxim in conversation between the main character, Moana and Maui in Moana movie, the maxim of relevance was the most identifiable type. 16 conversations cover 38,1%.  The second is the maxim  quantity. 14 conversations cover 33,3%. The third is the maxim manner. 10 conversation or covers 23,8%. The maxim quality gets 2 conversations and covers 4,8%. The conclusions are the conversation related to ask to do something, be success in doing something, give surprise and do not want something bad happened to the friend.Keywords: Conversational Maxims, Flouting Maxims, Movie